Penelusuran Struktur Cerita dalam Naskah Drama Terjemahan: Kasus "Badak-badak" karya Jim Lim - Hidayat, Arif; Zuriyati, Zuriyati; Anwar, Miftahulkhairah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
A translated drama script is a work that combines many elements from narrative structure to social and artistic aspects. Translating a drama script into another language requires a deep understanding of its cultural aspects, language and artistic nuances. This translation process not only changes the words, but also adjusts artistic elements, maintains the essence of the original story, and understands and reproduces the meaning contained in the drama. This research aims to comprehend the storyline in a translated drama script using the Traditional Narrative Analysis Method in the work "Badak-badak," a translation of "Rhinocéros" by Eugene Ionesco. The research results reveal that this manuscript carries the theme of the transformation of humans into rhinos with a linear plot that follows the chronology of events. Various key characters interact in a tavern as the main setting. The storyline visualization maps events from introduction to resolution, including Slamet's drinking routine, the appearance of the rhino, character transformation, and Slamet's state of isolation. This understanding influences many aspects, including learning, teaching, and theater practice. Storyline visualization provides a foundation for cultural exploration, deeper learning, and provides guidance in planning theatrical productions. An in-depth understanding of the storyline of a translated drama script not only enriches the learning experience of theater students, but also supports the design of a cohesive and strong theater production.Keywords – Badak-badak, Narrative Structure, Rhinoceros, Translated Drama Script.